[PP.15.03] MEASURE ACCURATELY, ACT RAPIDLY AND PARTNER WITH PATIENTS (MAP) IMPROVES HYPERTENSION CONTROL: PILOT-STUDY RESULTS FROM CARE COORDINATION INSTITUTE / AMERICAN MEDICAL ASSOCIATION. (September 2017) - Egan, B.; Hanlin, R.; Rakotz, M.; Asif, I.; Sutherland, S.; Yang, J.; Davis, R.; Bryan, S.; Wozniak, G.
Abstract : Objective: A quality improvement program to improve hypertension control with evidenced-based interventions for Measuring blood pressure (BP, mmHg) accurately, Acting rapidly to manage uncontrolled BP, and Partnering with patients to promote self-management of BP (MAP) was implemented in 2016 in a Family Medicine residency in South Carolina, United States. Design and method: Hypertensive patients were included in the study if they had a visit in the year before intervention (baseline period) and at least one visit during the six-month intervention period. Omron HEM-907 devices were used to measure BP with a checklist for positioning; if initial BP was > = 140/90, the automated office BP (AOBP) device was used to measure three additional BPs one minute apart with the patient alone in the examination room (measure accurately) and display the AOBP mean. When AOBP mean was > = 140/90, intensification of antihypertensive medications (act rapidly) took place and was assessed by the percent of visits with uncontrolled BP and no treatment change (therapeutic inertia). Facilitating BP self-monitoring and using affordable generic medications (partner with patients) was assessed indirectly by a reduction in systolic BP (SBP) per therapeutic change. Results: 714 hypertensive adults met inclusion criteria (mean age 54.4 years, 53.8% black, 66.0% female, 50.3% Medicaid). From baseline to the last intervention visit, BP control increased from 61.2% to 88.0% (p < 0.01). Among 277 uncontrolled hypertensive patients at baseline, mean systolic/diastolic BP fell from147/88 to 131/79 (p < 0.01/p < 0.01) and 80.5% (223/277) were controlled to < 140/90. For measuring accurately, SBP was 12.7 mmHg (p < 0.001) lower among the uncontrolled group with improved technique; while AOBP measurement showed a 2.5 mmHg (p < 0.05) lower SBP. Therapeutic inertia was unchanged (44.4% vs. 38.3%; p = 0.57); the reduction in SBP per therapeutic change increased from 8.3 mmHG to 21.6 mmHG (p < 0.01). Conclusions: MAP was associated with better hypertension control in a medically underserved population. Data indicate that measuring accurately and better patient engagement, i.e., greater decrease in SBP with each therapeutic change, accounted for improved hypertension control. Plans are in place to spread the program to 40 additional practices.